Survival of Salmonella and Enterococcus faecium in high fructose corn syrup and honey at room temperature (22 °C). (May 2021) - Alshammari, Jaza; Dhowlaghar, Nitin; Xie, Yucen; Xu, Jie; Tang, Juming; Sablani, Shyam; Zhu, Mei-Jun
Abstract: Salmonellosis has been frequently associated with the consumption of high-sugar, low-moisture foods. Honey and high fructose corn syrup (HFCS) are widely used liquid sugars that are added as humectants in low-moisture foods. The objective of this study was to determine the ability of Salmonella and its presumable surrogate, Enterococcus faecium NRRL B-2354, to survive in honey and HFCS during storage at room temperature (~22 °C). Using freeze-dried and lawn grown bacteria, the survival of Salmonella and E. faecium in honey and HFCS was determined. Regardless of the inoculation methods, more than 5 log10 reductions were observed in both bacteria in honey and HFCS after 21-days of storage at 22 °C. The pathogens and surrogate in honey and HFCS fell below the detectable limit after 28-days of storage. Thus, the tested bacteria are not able to survive in honey and HFCS over one-month storage at room temperature. The similar level of bacterial reduction in honey and HFCS in storage suggests that the main cause was not the commonly perceived antimicrobial agents in honey. In addition to high acidity of these liquid sugars, the extremely high osmotic pressure is likely the main reason for bacterial death in honey and HFCS during storage. The data provided useful information in developing effective microbial-safe strategies to be incorporated in the preparation or storage of low-moisture food and ingredients. Highlights: Salmonella strains were completely inhibited in honey and HFCS for 28 days at 22 °C. E. faecium strain reduction rate was as similar as Salmonella in honey and HFCS. Method of inoculation did not have significant effect on the survival of Salmonella. High osmotic pressure was the main killing factor for Salmonella in honey and HFCS.